Research on parameter optimization method of linear induction motor for rail transit based on kriging surrogate model - Dangchao Ge (Transportation Engineering, 2025)
To improve the output stability of linear induction motor for rail transit, this paper proposes a parameter optimization method based on the Kriging surrogate model. The dynamic characteristics of rail transit linear induction motor parameters are thoroughly analyzed, with particular focus on improving the harmonic permanent magnet flux linkage amplitude response. Motor voltage, current, and flux linkage are introduced as dynamic guidance fusion parameters, while the Kriging surrogate model is employed to adjust both fundamental wave and harmonic frequency conversion dynamics of the motor parameters, effectively suppressing harmonic oscillations and controlling the output stability of rail transit linear induction motors. The experimental results demonstrate that after implementing this optimization method, the torque-to-current ratio reaches its maximum value, stator copper consumption is significantly reduced, and torque ripple is effectively suppressed. The achieved minimum transmission delay of 0.638 ms represents a substantial performance advantage.